PZT-54 / 46 ferroelectric ceramic for improving direct current pulse voltage resistance through acid leaching pretreatment and preparation method of PZT-54 / 46 ferroelectric ceramic

By introducing an acid leaching pretreatment step into the solid-phase synthesis process and treating the ferroelectric ceramic raw materials with nitric acid solution, the problems of low powder purity and high oxygen vacancy concentration were solved, thereby improving the high pressure resistance of ferroelectric ceramics.

CN121226014APending Publication Date: 2025-12-30NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511338017.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

Ferroelectric ceramics prepared by traditional solid-state methods suffer from problems such as low powder purity, high oxygen vacancy concentration, and uneven microstructure, resulting in insufficient DC pulse withstand voltage performance.

Method used

An acid leaching pretreatment step was introduced into the solid-phase synthesis process. Pb3O4, ZrO2 and TiO2 powders were treated with analytical grade nitric acid solution to remove impurities and insoluble byproducts. Subsequently, they were evaporated, dried and ground to form high-purity precursor powders. Dense ferroelectric ceramics were prepared by pre-firing and sintering in a muffle furnace.

Benefits of technology

It significantly improves the powder purity and density of ferroelectric ceramics, enhances the uniformity of microstructure, and thus improves their DC pulse withstand voltage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121226014A_ABST
    Figure CN121226014A_ABST
Patent Text Reader

Abstract

The invention discloses a PZT-54 / 46 ferroelectric ceramic for improving direct current pulse voltage resistance through acid leaching pretreatment and a preparation method thereof, namely, Pb3O4 with the purity of 99.75%, ZrO2 with the purity of 99.6% and TiO2 with the purity of 99.72% are taken as original raw materials and are proportioned according to a stoichiometric ratio, 1mol% of Pb3O4 is additionally added to compensate lead volatilization, an analytically pure nitric acid solution is added into the mixture for pretreatment, and the PZT-54 / 46 ferroelectric ceramic is prepared through acid leaching pretreatment. And drying by distillation, drying and grinding, sintering in a muffle furnace to obtain compact ceramic, and finally coating a silver electrode and polarizing. Compared with a traditional solid phase method without acid leaching pretreatment, the leakage current density of the PZT ceramic prepared by the method is reduced, and the direct current pulse compression strength of the ceramic is improved. And the high-reliability PZT-54 / 46 ferroelectric ceramic with excellent voltage resistance and stable ferroelectric performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a PZT-54 / 46 ferroelectric ceramic with improved DC pulse withstand voltage performance through acid leaching pretreatment and its preparation method, belonging to the field of functional ceramic materials and electrical functional component preparation. Background Technology

[0002] Ferroelectric ceramics are a class of functional ceramic materials with spontaneous polarization properties, which can reverse or reorient under the influence of an applied electric field. These materials are widely used in core components such as capacitors, piezoelectric devices, and pyroelectric devices, and play a crucial role in navigation, general aviation, high-voltage, underwater acoustics, and electroacoustics. Especially in applications requiring high-amplitude, short-duration DC voltage pulses, such as piezoelectric igniters, shock wave generators, and pulse power switches, the DC pulse withstand voltage performance of ferroelectric ceramics directly determines the reliability, lifespan, and performance limits of the devices. Its withstand voltage performance relates to whether the device can avoid breakdown under ultra-high electric fields, whether it can suppress harmful domain flipping and losses, and whether it can maintain stable operation under harsh conditions. Therefore, improving the DC pulse withstand voltage performance of ferroelectric ceramics is of great significance for developing high-performance, high-reliability pulse power piezoelectric devices.

[0003] In the preparation of ferroelectric ceramics, powder quality and sintering process have a crucial impact on the final properties of the material. The traditional solid-state reaction method is widely used due to its simplicity, but it still suffers from problems such as insufficient powder purity, high levels of residual impurities, high oxygen vacancy concentration, and uneven grain distribution. These defects can lead to a decline in the electrical and mechanical properties of ceramics, thereby limiting their pressure resistance and long-term stability.

[0004] In existing research, various chemical pretreatment approaches have been proposed for impurity removal and purity improvement of ferroelectric ceramic precursor powders. For example, a common acid washing method involves briefly immersing raw material powders such as PbO, ZrO2, and TiO2 in dilute nitric acid, hydrochloric acid, or acetic acid to remove adsorbed carbonate and oxide impurities from the surface, thereby improving powder surface cleanliness and providing conditions for sintering. However, its removal effect is mostly limited to the surface layer, with limited improvement on deep defects. Another type of oxidant-assisted treatment method involves adding oxidants such as H2O2 to the acid solution, or directly treating the powder with hydrogen peroxide to remove low-valence impurities and repair oxygen vacancy defects. This can reduce conductivity and leakage current to some extent, but the treatment window is narrow, and excessive reaction can easily damage the powder structure. There is also a complexing agent-acid washing combined method, which adds complexing agents such as citric acid and EDTA to the dilute acid solution to enhance impurity removal. The carry-out effect of impurities helps improve the uniformity of powder composition, but there may be complexing agent residues, requiring thorough washing afterwards; otherwise, new impurities will be introduced during sintering. In addition, alkali treatment or ammonia treatment is also used for powder pretreatment to remove acid-insoluble impurities or adjust the surface chemistry of powder. Although it can effectively remove sulfates and chlorides in some systems, strong alkaline environments may corrode the crystal lattice and introduce new defects. Some studies have also proposed surface modification or coating removal methods, that is, first forming a removable coating layer (such as SiO2 sol or organic salt) on the powder surface, and then eluting or decomposing it at low temperature to indirectly remove impurities. This method has a certain effect on improving dispersibility and purity, but the process is complex, costly, and prone to residues.

[0005] While the aforementioned methods have improved the microstructure and voltage withstand performance of ferroelectric ceramics to some extent, they still suffer from problems such as complex processes, high costs, or limited improvement effects. Therefore, introducing a simple and effective pretreatment step into the solid-state synthesis route to effectively remove impurities, reduce oxygen vacancies, and improve powder purity has become an urgent need to enhance the DC pulse voltage withstand performance of ferroelectric ceramics. Summary of the Invention

[0006] This invention addresses the problems of insufficient DC pulse withstand voltage performance, low powder purity, high oxygen vacancy concentration, and inhomogeneous microstructure in ferroelectric ceramics prepared by traditional solid-state methods. It proposes an acid-leaching pretreatment method to improve the DC pulse withstand voltage performance of PZT-54 / 46 ferroelectric ceramics and its preparation method. By introducing an acid-leaching step into the solid-state synthesis process, this invention improves the density and DC pulse withstand voltage performance of the ceramic.

[0007] The technical solution for realizing the present invention is:

[0008] This invention provides a method for preparing PZT-54 / 46 ferroelectric ceramics with improved DC pulse withstand voltage performance through acid leaching pretreatment, comprising the following steps:

[0009] (1) Prepare Pb3O4, ZrO2 and TiO2 powders according to stoichiometric ratio. Add an extra 1 mol% of excess Pb3O4 powder relative to the required molar amount of Pb3O4 to compensate for lead volatilization.

[0010] (2) The above raw materials were placed in analytical grade nitric acid solution, stirred and reacted, and acid leaching was used to remove impurities and insoluble by-products. Then, they were evaporated, dried and ground to obtain high-purity precursor powder.

[0011] (3) The treated powder is pre-calcined in a muffle furnace to promote solid-phase reaction and form precursor phase;

[0012] (4) Grind the pre-fired powder thoroughly, press it into shape, and sinter it to obtain a dense ferroelectric ceramic block;

[0013] (5) A silver electrode is coated on the ceramic surface and a DC electric field is applied for polarization treatment to obtain a high-voltage ferroelectric ceramic sample.

[0014] Preferably, in step (1), the purity of Pb3O4 in the high-purity raw materials is 99.75%, the purity of ZrO2 is 99.6%, and the purity of TiO2 is 99.72%.

[0015] Preferably, in step (2), the acid leaching temperature is 60°C and the acid leaching time is 24h.

[0016] Preferably, in step (3), the pre-firing temperature is 800℃, the sintering rate is 1.6℃ / min, and the holding time is 2h.

[0017] Preferably, in step (4), the sintering temperature is 1200℃, the sintering rate is 0.25℃ / min, and the holding time is 2h.

[0018] Preferably, in step (5), the polarization electric field strength is 4kV / mm and the polarization time is 30min.

[0019] Another aspect of the present invention provides Pb(Zr) prepared by the above method. 0.54 Ti 0.46 O3 ferroelectric ceramics.

[0020] Compared with existing technologies, this invention introduces an acid leaching pretreatment step into the solid-state synthesis process, which can reduce impurity content and oxygen vacancy defects to a certain extent, thereby improving the purity and uniformity of the powder. The ceramic powder treated in this way is more easily densified during sintering, with a relatively uniform grain distribution, which helps to improve the DC pulse withstand voltage performance of ferroelectric ceramics. Attached Figure Description

[0021] Figure 1(a) PZT-54 / 46 ceramic sample after sintering; (b) PZT-54 / 46 ceramic sample after polarization.

[0022] Figure 2 (a) Surface image of PZT-54 / 46 powder before pre-firing; (b) Surface image of PZT-54 / 46 powder after pre-firing; (c) Surface image of the sintered sample at 100 μm; (d) Surface image of the sample at 20 μm.

[0023] Figure 3 XRD pattern of PZT-54 / 46 ceramic after acid leaching.

[0024] Figure 4 The relative permittivity and dielectric loss of PZT-54 / 46: (a) Relative permittivity as a function of frequency; (b) Dielectric loss as a function of frequency.

[0025] Figure 5 Dynamic and static hysteresis loops of the prepared PZT-54 / 46 at 3600V.

[0026] Figure 6 Leakage current performance of the prepared PZT-54 / 46. Detailed Implementation

[0027] The following embodiments illustrate the invention in more detail, but are not intended to further limit the invention.

[0028] This invention is based on Pb(Zr) 0.54 Ti 0.46 In the traditional solid-state synthesis process of O3 ferroelectric ceramics, an acid leaching pretreatment step is introduced to improve powder purity and ceramic density, thereby enhancing electrical and voltage withstand properties. Surprisingly, although nitric acid pretreatment does not introduce additional elements into the final material, it improves the uniformity of the ceramic's microstructure, resulting in a significant increase in its DC pulse withstand voltage. This invention provides a new process approach for improving the high-voltage reliability of ferroelectric ceramics, possessing both scientific and practical value.

[0029] Example 1

[0030] High-purity powders of Pb3O4, ZrO2, and TiO2 with purities of 99.75%, 99.6% for ZrO2, and 99.72% for TiO2 were taken. The powders were then processed according to the Pb(ZrO2)... 0.54 Ti 0.46 O3 was weighed according to stoichiometry (Pb excess 1 mol%) and added to 200 mL of analytical grade nitric acid (98%) solution. The solution was then magnetically stirred at 60 °C for 24 h. Subsequently, the solution was evaporated to dryness, dried, and ground into powder.

[0031] The powder was placed in a muffle furnace and heated to 800℃ at a rate of 1.6℃ / min, holding for 2 hours to complete the pre-sintering. After thorough grinding and passing through a 20μm sieve, it was pressed into discs approximately 20mm in diameter and 1mm thick. During sintering, the temperature was first increased to 800℃ at a rate of 1.6℃ / min, then increased to 1200℃ at a rate of 0.25℃ / min, and held for 2 hours. For polarization, silver electrodes were coated on both sides of the sintered sample, and after sintering at 600℃ for 30 minutes, it was polarized in an electric field of 4kV / mm for 30 minutes. The sample was then obtained.

[0032] Table 1 DC withstand voltage test results of PZT-54 / 46 ceramics after acid leaching pretreatment

[0033]

[0034] As shown in Table 1, the effective breakdown voltage of most samples is concentrated in the range of 4.3–5.6 kV / mm, exhibiting good DC pulse withstand voltage performance. Some samples remained stable at higher voltages, with their effective breakdown voltage further increasing. For example, the sample with a thickness of 1.056 mm achieved a breakdown voltage of 7.0 kV, corresponding to an effective breakdown voltage of 6.62 kV / mm. This indicates that acid leaching effectively improved the pulse withstand voltage performance of the ceramics.

[0035] Example 2

[0036] Take high-purity Pb3O4, ZrO2, and TiO2 powders, and mix them according to the formula: Pb(ZrO2) 0.54 Ti 0.46 O3 was weighed according to stoichiometric ratio (Pb excess 1 mol%) and added to 200 mL of aqueous solution. The solution was then magnetically stirred at 60 °C for 24 h. Subsequently, the solution was evaporated to dryness, dried, and ground into powder.

[0037] The powder was placed in a muffle furnace and heated to 800℃ at a rate of 1.6℃ / min, holding for 2 hours to complete the pre-calcination. After thorough grinding and passing through a 20μm sieve, it was pressed into discs approximately 20mm in diameter and 1mm thick. During sintering, the temperature was first increased to 800℃ at a rate of 1.6℃ / min, then increased to 1200℃ at a rate of 0.25℃ / min, and held for 2 hours. For polarization, silver electrodes were coated on both sides of the sintered sample, and after sintering at 600℃ for 30 minutes, it was polarized in an electric field of 4kV / mm for 30 minutes. The resulting sample was then obtained. The effective breakdown voltage of the untreated sample was approximately between 2.3-3.6kV / mm.

[0038] Example 3

[0039] Under the same conditions as in Example 1, the effects of different acid leaching temperatures on the material properties were examined, and the experimental results are shown in Table 2. In this example, 98% nitric acid was used as the acid leaching medium, and the acid leaching time was kept constant at 24 hours. The raw material powder was treated at 25℃, 40℃, 60℃, and 80℃ respectively. After washing and drying, the powder was pre-fired and sintered according to the solid-state reaction process. The DC pulse withstand voltage performance of the obtained ceramic samples was tested, and the results are shown in Table 2.

[0040] Table 2. Effect of different acid leaching temperatures on the compressive strength of ceramics

[0041]

[0042] As shown in the table, the acid leaching temperature of 60℃ yields the best results, with the obtained PZT-54 / 46 ferroelectric ceramic achieving a DC pulse withstand voltage of 6.62kV / mm. If the temperature is too low, impurities will not be completely removed, resulting in limited effectiveness; if the temperature is too high, it may lead to localized decomposition of the powder, excessive surface corrosion, or nitric acid volatilization, which would be detrimental to performance improvement.

[0043] Example 4

[0044] Under the same conditions as in Example 1, the effects of different acid leaching times on the material properties were examined, and the results are shown in Table 3. In this example, 98% nitric acid was used as the acid leaching medium, and the acid leaching temperature was kept constant at 60°C. Different acid leaching times (3h, 6h, 12h, 24h, 48h) were set to treat the raw material powder. After washing and drying, the powder was pre-fired and sintered using a solid-state reaction process. The DC pulse withstand voltage performance of the obtained ceramic samples was tested, and the results are shown in Table 3.

[0045] Table 3. Pressure resistance of samples under different acid leaching times

[0046]

[0047]

[0048] As shown in Table 3, the performance is optimal when the acid leaching time is 24 hours.

[0049] Experimental results show that the PZT-54 / 46 ferroelectric ceramic prepared in this invention exhibits certain improvements and potential advantages in terms of structure and electrical properties. XRD diffraction results show that the sample has a relatively pure crystal phase with clear diffraction peaks and no obvious impurity peaks, indicating that acid leaching helps reduce impurity phases and improve crystallinity. Regarding dielectric properties, test results show that the sample maintains a relatively stable dielectric constant in the low-to-high frequency range, with a dielectric loss of approximately 0.02–0.05, exhibiting good insulation characteristics and frequency stability, demonstrating its potential for application in high-frequency or high-voltage environments. Regarding ferroelectric properties, its PE hysteresis curve shows good symmetry and polarization reversibility, with a polarization intensity of approximately 1.8 μC / cm. 2 The level indicates that domain inversion is relatively stable. Regarding leakage current characteristics, the sample exhibits a leakage current density of less than 0.01 μC / cm² in the 100–500 V range. 2 Furthermore, the curve is stable without significant transitions, indicating that the breakdown channel is suppressed to some extent, which helps maintain a relatively stable working state under high voltage. Overall, these results suggest that acid leaching pretreatment has a positive effect on improving the comprehensive performance of ceramic materials. The process steps of this invention are relatively simple, the conditions are moderate, and it has certain application value.

[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent substitutions, and improvements made by those skilled in the art to the above embodiments without departing from the scope of the technical solution of the present invention, based on the technical essence of the present invention, shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A preparation method of PZT-54 / 46 ferroelectric ceramics with improved direct current pulse withstand voltage performance by acid leaching pretreatment, characterized in that, The method comprises the following steps: The Pb3O4 with a purity of 99.75%, the ZrO2 with a purity of 99.6% and the TiO2 with a purity of 99.72% are mixed according to a stoichiometric ratio, and then are stirred and acid-leached in an analytical pure nitric acid solution at 60 DEG C, and after being evaporated, dried and ground, the mixture is pre-fired at 800 DEG C, and then is sintered at 1200 DEG C for 2 hours, and then a silver electrode is coated on the ceramic surface and polarization is carried out, so that the high-voltage-resistant PZT-54 / 46 ceramic is obtained.

2. The method of claim 1, wherein, The Pb3O4, the ZrO2 and the TiO2 are high-purity raw materials, the purity of the Pb3O4 is 99.75%, the purity of the ZrO2 is 99.6% and the purity of the TiO2 is 99.72%.

3. The method of claim 1, wherein, The concentration of the nitric acid used in the acid-leaching pretreatment is 98%, the temperature is 60 DEG C, and the stirring reaction is continuously carried out, and the acid-leaching time is 24 hours.

4. The method of claim 1, wherein, 1mol% of excess Pb3O4 powder is additionally added relative to the molar calculated amount of the required Pb3O4.

5. The method of claim 1, wherein, The pre-firing temperature is 800 DEG C, the heating rate is 1.6 DEG C / min, and the holding time is 2 hours.

6. The method of claim 1, wherein, The sintering temperature is 1200 DEG C, the heating rate is 0.25 DEG C / min, and the holding time is 2 hours.

7. The method of claim 1, wherein, The polarization electric field intensity is 4kV / mm, and the polarization time is 30 minutes.

8. The method of claim 1, wherein, The method comprises the following steps: (1) Pb3O4, ZrO2 and TiO2 powders are prepared according to a stoichiometric ratio, and 1mol% of excess Pb3O4 powder is additionally added relative to the molar calculated amount of the required Pb3O4 to compensate for the volatilization of lead; (2) the above raw materials are placed in an analytical pure nitric acid solution, and are stirred and acid-leached to remove impurities and insoluble by-products, and then are evaporated, dried and ground to obtain high-purity precursor powders; (3) the treated powders are pre-fired in a muffle furnace to promote solid-phase reaction and form a precursor phase; (4) the pre-fired powders are fully ground, are pressed into a shape, are sintered to obtain a dense ferroelectric ceramic block; (5) a silver electrode is coated on the ceramic surface, and a direct-current electric field is applied for polarization treatment to obtain a high-voltage-resistant ferroelectric ceramic sample.

9. Pb(ZrTi)03 ferroelectric ceramics prepared by the production process according to any one of claims 1 to 8. 0.54 Ti 0.46 )O3